Towards sustainable vector control: Innovative substrate identification for developing eco-friendly, cost-effective, and highly potent biopesticides - Fatma Benjeddou; Ines Mnif; Marie Rossignol; Dhouha Ghribi; Slim Tounsi; Fabrice Chandre; Raida Zribi-Zghal (Biological Control)
The unavailability of biological insecticides for mosquitoes’ control in Tunisia and their high cost make chemical pesticides the most used solution. In the present study, the development of a bio-sourced media based on agriculture by-product and free biological material was conducted for the generation of commercially valuable biopesticide from BUPM98 Bacillus thuringiensis israelensis strain. Through the physico-chemical characterization of the spineless Opuntia ficus-indica cladodes flour (SFI flour), an important total organic carbon rate (18.92 %) was detected. Thus, SFI flour was used as a potential carbon source for B. thuringiensis cells growth and delta-endotoxin production. A bio-sourced media based on diluted sea water, SFI flour and soybean meal, was optimized for BUPM98 delta-endotoxin production through the response surface methodology. The adjusted medium improved the production by 58 % compared to the reference medium. Moreover, an additional improvement of 22.85 % in delta-endotoxin synthesis was achieved through cultivating BUPM98 in 1 L shake flasks with baffles under optimal conditions. This enabled the biopesticides production in the novel medium (FPOM-SFI) to reach 2405.5 ± 45 mg/L. Interestingly, the FPOM-SFI(BUPM98) achieved a more than threefold activity than VectoBac®12AS. In fact, it revealed LC50 values of 0.0039 mg/L and 0.0041 mg/L, against Aedes aegypti and Anophele gambiae larvae, respectively. These findings underscore the substantial potential of the BUPM98 based bio-pesticide produced in an almost bio-sourced medium for mosquito management in Tunisia as well as in North African countries, as an economical and eco-friendly alternative of chemical insecticides. FPOM-SFI(BUPM98) could be a sustainable and affordable pest control solution.